PENERAPAN MODEL INKUIRI TERBIMBING DALAM MENINGKATKAN MODEL MENTAL DAN PENGUASAAN KONSEP SISWA - Dewi Mawarni; Ratu Betta Rudibyani; Tasviri Efkar (Universitas Lampung, 2015)
The research was aimed to describe the effectiveness and effect size of guided inquiry model to the improvement of students mental models and concept mastery. This research used pre-experimental method with one group pretest-posttest design and by using cluster random sampling, it was obtained the 10th grade-10 in SMAN 1 Natar as sample class. The results shown that the effectiveness of guided inquiry learning model had a